Male Reception Towards Masculinity Construction on L-MEN’s Instagram Social Media - Izdihar Khalisha, Annisa; Dwiningtyas, S.Sos, MA, Dr. Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
This research envisages information about how the construction of masculinty showed on @LMEN’s Instagram influences male’s perspective in case of the ideal appearance of masculinity. The purposes of this research are to analyze how @LMEN’s Instagram constructs the male’s masculinity and how the man interprets those of masculinity concepts. Critical paradigm is used to analyze this research, furthurmore, this research also uses reception analysis method written by Ien Ang. Muscular Male Body Ideal Theory Susan Bordo and Disciplining The Body Theory Michel Foucault used as a theory that explains how the criteria muscular body as a symbol of men’s masculinity develops in the privacy and public, as well as the disciplinary body of what is being done to meet the image of the ideal man who constructed by media. The results showed the informant meaning of the meaning of dominant (preferred reading) have a diversity of meanings for different background influenced, among others, by categories of weight, age and occupation. Preferred reading offered on medium text Instagram is a man to be conducted disciplinary body form of exercise regime using the tool weights at the gym and taking supplements of L-MEN to have a muscular body (mesomoprh) to be recognized masculinity, a male figure that is ideal, strong, inspire, attractive, handsome and sexy. There are groups of informants men who have the same meaning with the dominant meaning, and there are groups that have meaning outside of the dominant meaning because it is associated with an internal value on themselves. And the informant dominant group are those who accept the dominant meaning of the text media from Instagram L-MEN.